Открытые дали: [стихи] / Виктор Федотов - Федотов Виктор Иванович (Советский писатель, 1986)
Экземпляры: КХ (20120609) / Инвентарный номер: 869702 / Цена: 0.40 / Сис.шифр: Р2 / Авт.знак: Ф 34 / ГРНТИ: 17 / ББК: 84(2)